Users' awareness of factors associated with complications during pill use - Petta, C. A.; Faúndes, A.; Pastene, L.; Pinotti, J. A. (Springer Nature, 1994)
This study compared the frequency of factors and diseases that contribute to the risks of oral contraceptive use among current users and non-users of oral contraception in order to evaluate the users' awareness of factors associated with complications during oral contraceptive use. Data from 5317 current users and 8863 non-users in the state of São Paulo, Brazil, were collected using questionnaires requesting information on the following variables: use of oral contraceptives, age, weight, smoking status, and the presence or history of hypertension, diabetes, cardiopathies, painful varicose veins, and epilepsy. Half of the users had some risk factors, and 17.4% were at high risk of complications from oral contraceptive use. Risk factors and diseases which appeared to be poorly known by the population as increasing the risk of oral contraceptive use were smoking, hypertension and painful varicose veins. Only a small percentage of the population appeared to know that these diseases and factors could increase the risk of health problems during oral contraceptive use. The results suggest a lack of information among users and providers on factors which are associated with an increased risk of health problems during use of oral contraceptives. © 1994 Kluwer Academic Publishers.